Achieving optimal adherence to medical therapy by telehealth: Findings from the ORBITA medication adherence sub‐study. Issue 1 (11th February 2021) - Thompson, David; Al‐Lamee, Rasha; Foley, Michael; Dehbi, Hakim M.; Thom, Simon; Davies, Justin E.; Francis, Darrel P.; Patel, Prashanth; Gupta, Pankaj; ,
Abstract: Introduction: The ORBITA trial of percutaneous coronary intervention (PCI) versus a placebo procedure for patients with stable angina was conducted across six sites in the United Kingdom via home monitoring and telephone consultations. Patients underwent detailed assessment of medication adherence which allowed us to measure the efficacy of the implementation of the optimization protocol and interpretation of the main trial endpoints. Methods: Prescribing data were collected throughout the trial. Self‐reported adherence was assessed, and urine samples collected at pre‐randomization and at follow‐up for direct assessment of adherence using high‐performance liquid chromatography with tandem mass spectrometry (HPLC MS/MS). Results: Self‐reported adherence was >96% for all drugs in both treatment groups at both stages. The percentage of samples in which drug was detected at pre‐randomization and at follow‐up in the PCI versus placebo groups respectively was: clopidogrel, 96% versus 90% and 98% versus 94%; atorvastatin, 95% versus 92% and 92% versus 91%; perindopril, 95% versus 97% and 85% versus 100%; bisoprolol, 98% versus 99% and 96% versus 97%; amlodipine, 99% versus 99% and 94% versus 96%; nicorandil, 98% versus 96% and 94% versus 92%; ivabradine, 100% versus 100% and 100% versus 100%; and ranolazine, 100% versus 100% and 100% versus 100%. Conclusions: Adherence levels were high throughout the study when quantified by self‐reporting methods and similarly high proportions of drug were detected by urinary assay. The results indicate successful implementation of the optimization protocol delivered by telephone, an approach that could serve as a model for treatment of chronic conditions, particularly as consultations are increasingly conducted online. Abstract : Medical therapy for patients with stable angina optimised over 6 weeks of tele‐ health clinic visits. Treatment titrated to home blood pressure and heart rate measurements. Medication adherence confirmed using HPLC MS/MS and patient self‐reporting. Patients subsequently randomised to PCI or placebo procedure in the ORBITA trial. Adherence reassessed at final follow‐up. Self‐reported adherence was >96% for all drugs in both treatment groups at both stages. Proportion of expected drug detected was >90% for all first‐choice, protocol‐directed medicines at both stages. No significant between group differences at pre‐ randomisation or at follow‐up and medication taking patterns did not change following treatment with PCI. The study uses a simple model for optimisation of medical therapy in clinical practice using a telehealth approach with high levels of adherence.